PENGARUH MODAL INTELEKTUAL TERHADAP PERTUMBUHAN KOPERASI KOTA KUPANG - Jems Arison Zachrias; Renya Rosari (Universitas Airlangga, 2019)
The purpose of this study is to find the effect of intellectual capital on the growth of cooperatives in Kupang City. Quantitative method is used in this study while data is taken from the cooperative's financial statement from 2011-2017. The intellectual capital is measured by Value Added Intellectual Coefficient (VAIC) while cooperative growth is measured by natural logarithm of the change in cooperative's total assets. The population in this study is all cooperatives that registered in Dinas Koperasi Kota Kupang, totaled 64 cooperatives and 6 cooperatives chosen as the sample using purposive sampling method. The results showed that Intellectual Capital have significant effect on the growth of cooperatives in Kupang City. The theoritical implication shows that indicators in VAIC can be applied in measuring the cooperatives’ growth. As the practical implication, this study offer insight for the decision maker in order to increase the growth of cooperatives in Kupang City.